Peran Mahasiswa Prodi KPI STAIN MADINA Dalam Mensukseskan Gerakan Say No To Drugs - Sahara Nurfitri; Marlina (MADANI PUBLISHER INDONESIA, 2025)
Drugs play a very active role as the biggest threat to the nation's future generations. Just as drug abuse and traf icking has grown rapidly in various circles, even more so now it has developed among students. As the next generation of the nation, students must be able to become agents of change for society in an ef ort to reject drugs. By carrying out activities to prevent drugs, one of them is by being active in making the Say To Drugs movement a success. This research examines the role of KPI STAIN Mandailing Natal students in the success of the